High‐intensity interval training improves cardiomyocyte contractile function and myofilament sensitivity to intracellular Ca 2+ in obese rats - dos Santos, Matheus Corteletti; da Silva, Daniel Sesana; Cordeiro, Jóctan Pimentel; Domingos, Lucas Furtado; da Silva Gomes, Ezio Henrique; Nogueira, Breno Valentim; Bocalini, Danilo Sales; Lima Leopoldo, Ana Paula; Leopoldo, André Soares (Experimental physiology, 2024)
High‐intensity interval training (HIIT) has shown significant results in addressing adiposity and risk factors associated with obesity. However, there are no studies that investigate the effects of HIIT on contractility and intracellular Ca 2+ handling. The purpose of this study was to explore the impact of HIIT on cardiomyocyte contractile function and intracellular Ca 2+ handling in rats in which obesity was induced by a saturated high‐fat diet (HFD). Male Wistar rats were initially randomized into a standard diet and a HFD group. The experimental protocol spanned 23 weeks, comprising the induction and maintenance of obesity (15 weeks) followed by HIIT treatment (8 weeks). Performance was assessed using the maximum oxygen consumption test (). Evaluation encompassed cardiac, adipose and skeletal muscle histology, as well as contractility and intracellular Ca 2+ handling. HIIT resulted in a reduction in visceral area, an increase in , and an augmentation of gastrocnemius fibre diameter in obese subjects. Additionally, HIIT led to a decrease in collagen fraction, an increase in percentage shortening, and a reduction in systolic Ca 2+ /percentage shortening and systolic Ca 2+ /maximum shortening rates. HIIT induces physiological cardiac remodelling, enhancing the contractile function of cardiomyocytes and improving myofilament sensitivity to Ca 2+ in the context of obesity. This approach not only enhances cardiorespiratory and physical performance but also reduces visceral area and prevents interstitial fibrosis. What is the central question of this study? Does high‐intensity interval training (HIIT) enhance myocardial contractility in models of obesity induced by a saturated high‐fat diet, and does it promote an improvement in intracellular Ca 2+ handling (Ca 2+ influx and reuptake)? What is the main finding and its importance? HIIT, as a non‐pharmacological tool of short duration but high intensity, improves cardiovascular function and the sensitivity of myofilaments to intracellular Ca 2+ handling, as well as promoting a reduction in visceral fat area. Thus, the obesity‐induced impairment of the heart's contractile properties was partially prevented by an 8‐week HIIT programme.